The diabetes disease state management exemplar. - Melchior L; Carter B; Helsley A; Ernest JK; Friesner D (Nursing Economic$)
One relatively new method of providing care to patients with chronic disease is disease state management (DSM). Diabetes is particularly interesting to study because it is not only one of the most prevalent chronic diseases, but it is also a disease for which DSM is highly cost effective. Similarly, registered nurses represent the group of practitioners most likely to provide a comprehensive set of DSM activities. This experiment was conducted in fall 2005 at a nationally recognized diabetes center which is affiliated with a large, full service medical center The results suggest at least three forms of content delivery -- in-class, at-home study packets, and online modules -- are all equally effective at enhancing diabetes DSM knowledge.